2020
DOI: 10.1016/j.molcel.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Crossing over during Mouse Meiosis

Abstract: Highlights d Fine-scale mapping of heteroduplex DNA in mismatch repairdefective mice d Mismatch repair-mediated heteroduplex rejection is not evident during meiosis d Heteroduplex DNA patterns revise the canonical meiotic recombination model in mice d D-loop migration and asymmetric Holliday junction cleavage are intrinsic features

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…For example, crossover frequency measured at varying scales in mice did not change in msh2 or pms2 (Qin et al, 2002;Kolas et al, 2005;Peterson et al, 2020). Mouse msh2 mutants show heteroduplex retention in crossover products, but MSH2-dependent suppression of meiotic recombination was not observed (Peterson et al, 2020). Interestingly, this is in contrast to the anti-recombination role of MSH2 in mitotic cells observed during HR in both mouse and Arabidopsis (Elliott & Jasin, 2001;Emmanuel et al, 2006;Li et al, 2006).…”
Section: Of 22mentioning
confidence: 78%
See 1 more Smart Citation
“…For example, crossover frequency measured at varying scales in mice did not change in msh2 or pms2 (Qin et al, 2002;Kolas et al, 2005;Peterson et al, 2020). Mouse msh2 mutants show heteroduplex retention in crossover products, but MSH2-dependent suppression of meiotic recombination was not observed (Peterson et al, 2020). Interestingly, this is in contrast to the anti-recombination role of MSH2 in mitotic cells observed during HR in both mouse and Arabidopsis (Elliott & Jasin, 2001;Emmanuel et al, 2006;Li et al, 2006).…”
Section: Of 22mentioning
confidence: 78%
“…Finally, we note that msh2 meiotic recombination phenotypes differ between other species. For example, crossover frequency measured at varying scales in mice did not change in msh2 or pms2 (Qin et al, 2002;Kolas et al, 2005;Peterson et al, 2020). Mouse msh2 mutants show heteroduplex retention in crossover products, but MSH2-dependent suppression of meiotic recombination was not observed (Peterson et al, 2020).…”
Section: Of 22mentioning
confidence: 95%
“…cerevisiae also similarly indicate that even at 26% sequence divergence, loss of MMR leads to a 55-fold increase in mitotic recombination [ 72 , 73 ]. Conversely, studies in other models have observed instances where loss of Msh2 did not lead to increased recombination frequencies between substrates with as little as 1% sequence divergence, up to 25% divergence [ 74 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on mitotic recombination in S. cerevisiae also similarly indicate that even at 26% sequence divergence, loss of MMR leads to a 55-fold increase in mitotic recombination [72,73]. Conversely, studies in other models have observed instances where loss of Msh2 did not lead to increased recombination frequencies between substrates with as little as 1% sequence divergence, up to 25% divergence [7476].…”
Section: Discussionmentioning
confidence: 99%